2019
DOI: 10.16955/bitkorb.422417
|View full text |Cite
|
Sign up to set email alerts
|

Kavun sineğinin [Myiopardalis pardalina (Bigot, 1891) (Diptera: Tephritidae)] yumurta koymasına ve zarar şekline meyve büyüklüğünün etkisi

Abstract: Baluchistan melon fly [Myiopardalis pardalina (Bigot, 1891) (Diptera: Tephritidae)] is the most important pest of the melons (Cucumis melo L.) (Cucurbitaceae). The melon fly caused damage during the larval period by feeding the fruit core-cavity. The fruit damaged by larvae becomes brown and the color occurring in melon changes the taste and aroma of fruit. The aim of this research is to indicate eggs laying into the different fruit size and to determine the relationship between the larval exit hole and the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…According to the results of this study; The lowest population of Ananas melon variety was 0.63 insects / 3 plants. As a result of a study conducted by Barış and Çobanoğlu (2013), it was reported that the damage rates caused by the melon fly in İpsala and Kırkağaç melon kinds were around 20% in both kinds. The researchers also reported that there was no statistical difference between the varieties in terms of the damage caused by the melon fly.…”
Section: Determination Of Contamination Rate Of the Melon Fly In Land...mentioning
confidence: 99%
“…According to the results of this study; The lowest population of Ananas melon variety was 0.63 insects / 3 plants. As a result of a study conducted by Barış and Çobanoğlu (2013), it was reported that the damage rates caused by the melon fly in İpsala and Kırkağaç melon kinds were around 20% in both kinds. The researchers also reported that there was no statistical difference between the varieties in terms of the damage caused by the melon fly.…”
Section: Determination Of Contamination Rate Of the Melon Fly In Land...mentioning
confidence: 99%